2022
DOI: 10.1186/s12864-022-08320-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the first complete plastome genomics, comparative analyses, and phylogenetic dispositions of endemic medicinal plant Ziziphus hajarensis (Rhamnaceae)

Abstract: Background Ziziphus hajarensis is an endemic plant species well-distributed in the Western Hajar mountains of Oman. Despite its potential medicinal uses, little is known regarding its genomic architecture, phylogenetic position, or evolution. Here we sequenced and analyzed the entire chloroplast (cp) genome of Z. hajarensis to understand its genetic organization, structure, and phylogenomic disposition among Rhamnaceae species. Results The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
2
2
0
Order By: Relevance
“…The previous studies of Ziziphus showed that eight species of Ziziphus formed a stable monophylete, our results of phylogenetic analysis are consistent with this (Asaf et al. 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous studies of Ziziphus showed that eight species of Ziziphus formed a stable monophylete, our results of phylogenetic analysis are consistent with this (Asaf et al. 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“… 2017 ), Z. hajarensis MZ475300 (Asaf et al. 2022 ), Ziziphus attopensis MW201670 (Li 2021 ), Ziziphus mauritiana KY628304 (Huang et al. 2017 ), Ziziphus spina-christ KY628305 (Huang et al.…”
Section: Resultsmentioning
confidence: 99%
“…T. hamiensis var. qatarensis and T. simplex plastomes are almost similar in size to previously reported Tetraena and Zygophyllum plastomes 56 and significantly shorter than other angiosperms 57 59 . Both Tetraena plastomes had a quadripartite structure, standard in vascular plants 60 , and the GC content was similar to that of many other angiosperm species 59 , 61 .…”
Section: Discussionsupporting
confidence: 85%
“…Genetic variations in G. mangostana cultivars have been shown by randomly amplified DNA fingerprinting (RAF) and inter simple sequence repeat (ISSR) molecular markers [ 58 , 59 , 60 ]. Plastomes also contain SSR and long repeats [ 61 , 62 , 63 , 64 ]. SSR, which is a stretch of 1–6 bp small repeats, is found extensively in different regions of the plastome, such as the intergenic regions, intron regions, and protein-coding regions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%